1998
DOI: 10.1590/s0103-97331998000400008
|View full text |Cite
|
Sign up to set email alerts
|

Bilayer membranes with 2D-nematic order of the surfactant polar heads

Abstract: In this paper we review and discuss the possibility of having a 2D-nematic ordering of the surfactant polar heads in bilayer membranes. The coupling between the nematic order parameters and the curvature can yield instabilities in the shape of the membrane, generally leading to tubules with mesoscopic radiuses. The nematic directors in the two monolayers should present coupled disclinations with peculiar characteristics. Para-nematic membranes, i.e., nematic membranes that are in the isotropic phase when at, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 3 publications
0
25
0
Order By: Relevance
“…It was shown that at sublytic concentrations of amphiphiles in the RBC suspension, the anisotropic amphiphiles induce tubular membrane budding and the release of stable tubular microexovesicles [18,35,37,49,51], while most of the other amphiphile molecules induce small, predominantly spheroidal microexovesicles that are formed from small membrane buds [8,35,51,52]. The experimentally observed tubular budding and vesiculation of the RBC membrane [18,35,49,51] can be theoretically explained by deviatoric membrane properties due to the in-plane orientational ordering of anisotropic membrane inclusions [8,10,15,[53][54][55][56][57][58][59][60][61].…”
Section: Membrane Budding and Endovesiculationmentioning
confidence: 99%
See 2 more Smart Citations
“…It was shown that at sublytic concentrations of amphiphiles in the RBC suspension, the anisotropic amphiphiles induce tubular membrane budding and the release of stable tubular microexovesicles [18,35,37,49,51], while most of the other amphiphile molecules induce small, predominantly spheroidal microexovesicles that are formed from small membrane buds [8,35,51,52]. The experimentally observed tubular budding and vesiculation of the RBC membrane [18,35,49,51] can be theoretically explained by deviatoric membrane properties due to the in-plane orientational ordering of anisotropic membrane inclusions [8,10,15,[53][54][55][56][57][58][59][60][61].…”
Section: Membrane Budding and Endovesiculationmentioning
confidence: 99%
“…The orientational order in membranes could occur due to the anisotropic shape of membrane components like anisotropic proteins or lipids [8,53,56,[78][79][80]. A typical example of inclusions possessing nematic order [58] are anisotropic banana shaped BAR protein domains [11,81,82]. The orientational order often arises in highly curved parts of the membrane due to the alignment of these anisotropic components [8,51,76].…”
Section: Fission Of the Membrane Daughter Endovesiclesmentioning
confidence: 99%
See 1 more Smart Citation
“…We will show in the remainder of this section (and also in section 5) that a source for anisotropic bending energy will be the minimal requirement to explain the emergence and stability of tubular shapes, which could arise from an in-plane orientational field on the membrane [298, 299]. In general, the different types of intrinsic and extrinsic in-plane order, discussed in section 4.1, can be represented as a p -atic in-plane field.…”
Section: Modeling Membrane Proteins As Spontaneous Curvature Fieldsmentioning
confidence: 99%
“…[10][11][12] The protein distribution and their cooperative effect on membrane morphology has been theoretically investigated by extending the existing membrane models. [13][14][15][16] However, the realm of these theoretical models are restricted to axisymmetric membrane shapes and small deviations around it.…”
Section: Introductionmentioning
confidence: 99%